Model Komunikasi Advokasi Pencegahan Korupsi Pada Media Publikasi Humas Lembaga KPK - Jhanattan, Mohammad (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2020)
The communication strategy implemented by the KPK is to accurately and systematically use the media as a conveyor of advocacy. The partnership built by the KPK Public Relations team with the media crew is by giving official press releases. The excerpts from the press release come from elements of the Leadership, Spokesperson, Structural Officials, Advisors, and Prominence Person. Advocacy carried out through the media includes introducing KPK work programs, Anti-Corruption Education, Research and Development Study Results Reports (R & D), determining the status of suspects at press conferences and / or delivering the results of a sting operation. Especially for media that is managed independently by the KPK, through online services (live streaming) it has specificities, among others, to deliver news about the prosecution and prevention of corruption, discussion of anti-corruption law (Legal Clinic), educational shows for families and children, as well as contemporary content that contains things that are closely related to people’s daily lives. This form of live streaming can be re-recorded as Pod Cast (video recording on demand). In terms of the delivery technique as well as the content of the program, the responsibility for the content and copyright is fully owned by the KPK.